2015
DOI: 10.1021/jacs.5b06627
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Titanium Hydrazides with Silanes and Boranes: N–N Bond Cleavage and N Atom Functionalization

Abstract: Reaction of Ti(N2(iPr)N)(NNPh2)(py) with Ph(R)SiH2 (R = H, Ph) or 9-BBN gave reductive cleavage of the N(α)-N(β) bond and formation of new silyl- or boryl-amido ligands. The corresponding reactions of Cp*Ti{MeC(N(i)Pr)2}(NNR2) (R = Me or Ph) with HBPin or 9-BBN gave borylhydrazido-hydride or borylimido products, respectively. N(α) and N(β) atom transfer and dehydrogenative coupling reactions are also reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Only two examples of titanium have been reported, both being derived from non-conventional routes involving B–B, B–H, and B–C bond activation reactions. 52,79 Our ability to prepare nitride 1 allows us to explore simple salt-metathesis reactions to construct these archetypal functionalities. Hence, treating 1 with ClBcat (cat = catechol) resulted in clean conversion to the borylimido (PN) 2 TiN{Bcat} ( 6 ) in ∼89% yield after subsequent workup of the reaction mixture (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Only two examples of titanium have been reported, both being derived from non-conventional routes involving B–B, B–H, and B–C bond activation reactions. 52,79 Our ability to prepare nitride 1 allows us to explore simple salt-metathesis reactions to construct these archetypal functionalities. Hence, treating 1 with ClBcat (cat = catechol) resulted in clean conversion to the borylimido (PN) 2 TiN{Bcat} ( 6 ) in ∼89% yield after subsequent workup of the reaction mixture (Scheme 2).…”
Section: Resultsmentioning
confidence: 99%
“…Reaction of (NacNac NMe 2 )ScCl 2 (13) with 2 equiv of MeLi in THF, based on previous protocols, 5 formed (NacNac NMe 2 )ScMe 2 (14). In situ reaction of 14 with 1 and 2 equiv of 11 produced the methyl-borylamide (NacNac NMe 2 )Sc-(Me){NHB(N i Pr) 2 C 6 H 4 } (15) and the bis(borylamide) (NacNac NMe 2 )Sc{NHB(N i Pr) 2 C 6 H 4 } 2 (16), respectively. Thermolytic alkane elimination from primary amido-alkyl compounds is a well-established protocol for the synthesis of imido compounds for both the rare earths (vide supra) and the early transition metals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A fairly clear picture of the similarities and differences between ScNAr′ and the more widely studied Group 4 organoimido counterparts is starting to emerge. Our group has been interested in developing early transition metal-imido and related metal−ligand multiple bond chemistry, 2a,b,d,4b,14 and during the course of these studies we recently reported the serendipitous formation of a very rare 15 titanium borylimido compound 5 (Figure 2) 16 through the reductive N−N bond cleavage reaction of the hydrazide Cp*Ti{MeC-(N i Pr) 2 }(NNR 2 ) (R = Me or Ph) with 9-BBN. Prior to this, the only other terminal Group 4 borylimide known was Mindiola's 6, formed from the parent imide (i.e., terminal NH) with 2 equiv of NaHBEt 3 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recent reactivity studies of group 4 hydrazido complexes have focused on hydridic bond activation reaction of e.g. silanes and boranes . Consequently, we decided to investigate the reactivity of the titanocene hydrazido complex 2 toward sterically demanding boranes such as 9-borabicyclo[3.3.1]­nonane (9-BBN) and catecholborane.…”
Section: Resultsmentioning
confidence: 99%
“…They are known for a broad range of stoichiometric reactions with multiple-bond substrates such as alkynes, nitriles, isocyanides, isocyanates, carbon dioxide, carbon disulfide, etc. Furthermore, they can be used as catalysts for hydrohydrazination reactions and, as shown in recent studies, in activation reactions of hydride bonds of silanes and boranes . Especially the (reductive) cleavage of the N α –N β bond is of interest in these kinds of reactions, which offers completely new synthetic routes in contrast to the titanium imido complexes .…”
Section: Introductionmentioning
confidence: 99%